Transformasi Pendidikan Islam Melalui Pembiasaan di Sekolah Dasar: Kajian Berbasis Library Research: pendidikan pembiasaan - Eko Kurniawanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the concept of habituation in Islamic education as an effective strategy for shaping the character of elementary school students. Through a library research approach, this study analyzes relevant principles of Islamic education and their application in the context of modern education. The findings reveal that habituation based on Islamic values, such as honesty, discipline, responsibility, and tolerance, significantly impacts character development in students. Consistently implemented habituation methods, through exemplary practices and daily routines, have proven effective in internalizing these values. Innovations in habituation, such as the integration of digital technology, Qur'anic literacy, and flagship tahfidzul Qur'an programs, strengthen the implementation of character education in elementary schools. However, challenges such as limited resources, parental involvement, and technological adaptation require strategic solutions, including teacher training and multi-stakeholder collaboration. This study emphasizes that habituation in Islamic education is not only relevant but also adaptable to the needs of modern education, making it a transformational strategy for shaping a generation with noble character, knowledge, and integrity.